2023
DOI: 10.1002/anie.202304419
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanocomposites Camouflaged with Hybrid Cell Membranes for Accurate Therapy of Early‐Stage Glioma

Abstract: Glioma features high fatality rate and short survival time of patients due to its fast growth speed and high invasiveness, hence timely treatment of early‐stage glioma is extremely important. However, the blood brain barrier (BBB) severely prevents therapeutic agents from entering the brain; meanwhile, the non‐targeted distribution of agents always causes side effects to vulnerable cerebral tissues. Therefore, delivery systems that possess both BBB penetrability and precise glioma targeting ability are keenly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…It has been reported that adhesion molecules (eg adhesion proteins and integrins) on the surface of cancer cell membranes can confer homologous recognition and homing properties to nanomaterials. 38–40 This result confirms that the improved antitumor effect of the nanomaterials can be attributed to the homotypic targeting ability of DCM@GDY-CuMOF@DOX.…”
Section: Resultssupporting
confidence: 74%
“…It has been reported that adhesion molecules (eg adhesion proteins and integrins) on the surface of cancer cell membranes can confer homologous recognition and homing properties to nanomaterials. 38–40 This result confirms that the improved antitumor effect of the nanomaterials can be attributed to the homotypic targeting ability of DCM@GDY-CuMOF@DOX.…”
Section: Resultssupporting
confidence: 74%
“…A wide range of cell membrane combinations has been investigated for preparing Hym to encapsulate nanomaterials. Beyond the examples previously discussed, research has explored hybrids of cancer–cancer [ 91 ], DC–cancer [ 92 ], RBC–PLT [ 139 ], mitochondria–cancer [ 140 ], bacteria–cancer [ 141 ], and embryonic–bacteria [ 142 ], among others.…”
Section: Application Of Cell Membrane-coated Nanoparticles In Cancer ...mentioning
confidence: 99%
“…Chi et al proposed a hybrid cell membrane (HM) camouflage strategy consisting of brain metastatic breast cancer cell membranes MCF-7 cell membrane (MM) and U87-MG cell membrane (UM). The nano-delivery system has BBB cross-over capability and homologous tumor-targeting capability inherited from two cell membranes of origin [ 141 ]. In vitro and in vivo investigations have been carried out on the ability of HMGINPs to cross the blood–brain barrier ( Figure 9 G).…”
Section: Classification Of Cmbndsmentioning
confidence: 99%
“…Long circulation [139] Leukocyte-cancer cell Immune escaping Tumor-targeting [140,150] Cancer-cancer Transendothelial migration Tumor-targeting [141] Although CMBNDS has shown promising therapeutic prospects in cancer diagnosis and treatment, there are still some remaining problems in the development and clinical application of CMBNDS. Here we summarize the problems encountered in the development and clinical application of CMBNDS.…”
Section: Homologous Recognition Homing Characteristicsmentioning
confidence: 99%